Current Status of Platinum Based Nanoparticles: Physicochemical Properties and Selected Applications ‐ A Review. Issue 2 (1st April 2019) - Sakthivel, C.; Keerthana, L.; Prabha, I.
The present article reviews the synthesis routes and applications of platinum-based nanoparticles in emerging fields such as energy harvesting, health care applications and sensors. Increasingly, more useful, novel and multifunctional materials are needed with fewer side effects. This article provides an overview of Pt-based nanoparticles along with recent applications in electrochemistry, photochemistry, biosensors and gas sensors. In particular, platinum dioxide (Adams' catalyst) has been used in many chemical reactions including hydrogenation, oxidation and reduction.